Tingkat Kerawanan Kebakaran Hutan Dan Lahan Di Banjarbaru Provinsi Kalimantan Selatan - Muhammad Riza Saputra; Deasy Arisanty; Sidharta Adyatma (Jambura Geoscience Review, 2021)
One of the areas in South Kalimantan that is prone to land fires is the Banjarbaru area, especially on peatlands. The fire in Banjarbaru is important because of the vital object of Syamsudin Noor Airport. Mapping of fire vulnerability was important for the Banjarbaru area, which had repeated fires throughout the year. The objective of the study was to analyze the vulnerability of forest and land fires in Banjarbaru, South Kalimantan Province. This study used Landsat 8 Oli Tirs imagery to obtain NDVI data and land cover maps from INA-Geoportal. The analysis of data used the scoring and overlay of the two maps. The level of vulnerability was dominated by the high vulnerability. The high level of vulnerability in Cempaka District was 81.9 %, in Banjarbaru Selatan District was around 99.5 %, in Banjarbaru Utara District was around 95.3 %, in Landasan Ulin District was around 94.1 % and in Lianganggang District was around 88.9 %. Land cover in the form of agriculture, plantations, and shrubs with moderate-high density caused the land to be more prone to fires.